2014
DOI: 10.3390/ijerph110909811
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunomagnetic Separation for the Detection of Salmonella in Surface Waters by Polymerase Chain Reaction

Abstract: Salmonella spp. is associated with fecal pollution and capable of surviving for long periods in aquatic environments. Instead of the traditional, time-consuming biochemical detection, polymerase chain reaction (PCR) allows rapid identification of Salmonella directly concentrated from water samples. However, prevalence of Salmonella may be underestimated because of the vulnerability of PCR to various environmental chemicals like humic acid, compounded by the fact that various DNA polymerases have different susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The presence of high background indigenous microflora and complex matrix in food also limits detection of pathogen from food samples. Again, pathogen often exist in viable but non-culturable states in food which cannot be detected by the conventional culture based method [ 5 ]. There is a great need for improved methods for foodborne pathogen detection in food matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high background indigenous microflora and complex matrix in food also limits detection of pathogen from food samples. Again, pathogen often exist in viable but non-culturable states in food which cannot be detected by the conventional culture based method [ 5 ]. There is a great need for improved methods for foodborne pathogen detection in food matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Although plasma biomarkers are less invasive and more cost-effective than CSF biomarkers, plasma biomarker data from Fortea et al’s study were nonconclusive. We recently developed a technology called immunomagnetic reduction (IMR), which is capable of assaying molecules at very low concentrations. We have used this technology to evaluate plasma biomarkers in AD and DS patients and healthy controls, and demonstrated a decrease in Aβ40 and increase in Aβ42 levels in AD patients, a large increase Aβ40 and decrease in Aβ42 levels in DS patients with no dementia, and a decline in Aβ40 and tau and rise in Aβ42 levels in DS patients with dementia . In that study, we suggested that either Aβ40 or Aβ42/Aβ40 can be biomarkers for neurodegeneration in DS.…”
Section: Introductionmentioning
confidence: 99%
“…IMS employing superparamagnetic MPs coated with specific antibody has become an essential tool for high-throughput and low-cost enrichment/isolation of various biomolecules and cells from heterogeneous samples. Examples of IMS applications are: (i) extraction of bacterial cells from the food/biological samples followed by detection using real-time PCR [2][3][4][5][6][7] or mass spectrometry (MS) analysis [8][9][10], (ii) positive selection/removal of specific cells from blood, bone marrow and other biological samples [11][12][13][14][15][16][17][18][19][20], (iii) capturing and detection of clinically important protein biomarkers [21][22][23][24], etc. To increase the sensitivity IMS can also be performed in a microfluidic arrangement [25][26][27] or may be combined with detection using quantum dots (QDs) [28][29][30].…”
Section: Introductionmentioning
confidence: 99%